Analysis of Learning Difficulties in Mandarin Among Fifth-Grade Students at Gembala Baik II Elementary School - Charlene Charlene; Lily Thamrin; Lusi Lusi (Universitas Muhammadiyah Enrekang, 2024)
This study aims to analyze the various difficulties faced by fifth-grade students at Gembala Baik II School in learning Mandarin. Mandarin is a language that requires mastery of listening, speaking, reading, and writing skills. However, many students encounter significant challenges, particularly in grammar, pronunciation, and the complex structure of Chinese characters. Additionally, students' lack of confidence in actively and interactively using the language contributes to their learning difficulties. This research adopts a qualitative approach, utilizing questionnaires and interviews conducted with 38 students. The data were analyzed descriptively to identify common patterns in the difficulties experienced by the students. The findings indicate that, aside from linguistic challenges, external factors such as teaching methods and classroom environment significantly impact students' understanding. It is recommended that teachers adopt more creative and interactive teaching approaches, such as simulations and language games, to enhance student engagement and help them overcome their learning challenges in Mandarin. This study aims to contribute to the development of more effective teaching strategies for foreign language classrooms, particularly in Mandarin instruction